The Mediating Role of Employee Engagement in the Relationship between Green Human Resource Management and Organizational Sustainability Performance - Juliet Pauladel Truly Makinggung; Jufrina Mandulangi (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study investigates the mediating role of employee engagement in the relationship between Green Human Resource Management (GHRM) practices and organizational sustainability performance. Drawing on social exchange theory and the ability-motivation-opportunity (AMO) framework, we propose that GHRM initiatives (green recruitment, training, performance management, and empowerment) foster employee engagement, which in turn enhances environmental, social, and economic sustainability outcomes. Using survey data from 312 middle-level managers in manufacturing and service sectors, structural equation modeling (SEM) was employed to test the hypothesized model. Results indicate that GHRM has a significant positive direct effect on sustainability performance, and employee engagement partially mediates this relationship (indirect effect β = 0.27, p < 0.001). The findings highlight that engaged employees act as active agents who translate organizational green policies into tangible sustainability gains. Theoretical and practical implications are discussed, emphasizing the need for organizations to invest in engagement-centric GHRM strategies.KEYWORDSGreen Human Resource Management, employee engagement, organizational sustainability performance, triple bottom line, mediation analysis, AMO theory Penelitian ini menyelidiki peran mediasi dari keterikatan karyawan (employee engagement) dalam hubungan antara praktik Manajemen Sumber Daya Manusia Hijau (Green Human Resource Management / GHRM) dan kinerja keberlanjutan organisasi. Berdasarkan teori pertukaran sosial (social exchange theory) dan kerangka kerja ability-motivation-opportunity (AMO), kami mengusulkan bahwa inisiatif GHRM (rekrutmen hijau, pelatihan, manajemen kinerja, dan pemberdayaan) mendorong keterikatan karyawan, yang pada gilirannya meningkatkan hasil keberlanjutan lingkungan, sosial, dan ekonomi. Menggunakan data survei dari 312 manajer tingkat menengah di sektor manufaktur dan jasa, pemodelan persamaan struktural (structural equation modeling / SEM) digunakan untuk menguji model yang dihipotesiskan. Hasil penelitian menunjukkan bahwa GHRM memiliki efek langsung positif yang signifikan terhadap kinerja keberlanjutan, dan keterikatan karyawan memediasi sebagian hubungan ini (efek tidak langsung β = 0,27, p < 0,001). Temuan ini menyoroti bahwa karyawan yang terikat bertindak sebagai agen aktif yang menerjemahkan kebijakan hijau organisasi menjadi perolehan keberlanjutan yang nyata. Implikasi teoretis dan praktis dibahas, dengan menekankan perlunya organisasi untuk berinvestasi dalam strategi GHRM yang berpusat pada keterikatan (engagement-centric). Kata KunciManajemen Sumber Daya Manusia Hijau, keterikatan karyawan, kinerja keberlanjutan organisasi, triple bottom line, analisis mediasi, teori AMO